Leafy greens : an A to Z guide to 30 types of greens plus more than 120 delicious recipes - Bitman, Mark (John Wiley, 2012)
Addressing the need for flavorful, antioxidant-rich foods, a collection of recipes highlights thirty leafy green vegetables that complement such suggestions as crispy-skin salmon on a bed of gingery kale and hot and sour bok choi.